2016
DOI: 10.3390/nano6100187
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of CO and Methanol on Pd-Ni Catalysts Supported on Different Chemically-Treated Carbon Nanofibers

Abstract: In this work, palladium-nickel nanoparticles supported on carbon nanofibers were synthesized, with metal contents close to 25 wt % and Pd:Ni atomic ratios near to 1:2. These catalysts were previously studied in order to determine their activity toward the oxygen reduction reaction. Before the deposition of metals, the carbon nanofibers were chemically treated in order to generate oxygen and nitrogen groups on their surface. Transmission electron microscopy analysis (TEM) images revealed particle diameters betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Therefore, transition metal oxides and their composites have attracted considerable attention as electrocatalysts due to their low electrical resistance, low cost, easy preparation, and excellent catalytic activity [15][16][17][18]. From among these metal oxide composites, nickel-based materials are emerging as one of the most promising candidates due to their chemical stability, electrical properties, and the ability to remove intermediate CO ad in alkaline media [19][20][21]. Several researchers have demonstrated that the addition of non-precious metallic materials, complexes, and oxides with nickel-based catalysts has increase catalytic activity and durability [22].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, transition metal oxides and their composites have attracted considerable attention as electrocatalysts due to their low electrical resistance, low cost, easy preparation, and excellent catalytic activity [15][16][17][18]. From among these metal oxide composites, nickel-based materials are emerging as one of the most promising candidates due to their chemical stability, electrical properties, and the ability to remove intermediate CO ad in alkaline media [19][20][21]. Several researchers have demonstrated that the addition of non-precious metallic materials, complexes, and oxides with nickel-based catalysts has increase catalytic activity and durability [22].…”
Section: Introductionmentioning
confidence: 99%
“…In DMFC, methanol is oxidized to produce H + , e − , and CO 2 according to the reaction formula CH 3 OH + H 2 O CO 2 + 6H + + 6e − . However, carbon–oxygen bonds in methanol are not easy to break, so the methanol electro-oxidation reaction (MOR) on the anode is critical to the overall performance of DMFCs [ 10 , 11 ]. Pt-based alloys are widely used as highly reactive anode catalysts as an important component of DMFCs [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Relative to traditional activated carbon, an ACF material has the advantages of larger specific surface area, higher pore size, more stable performance, faster adsorption rate, and larger adsorption capacity. These advantages cause the ACFs to have a wide application potential in wastewater treatment [28,29]. Yu et al [30] optimized and improved a nitric acid oxidation process by using microwaves and sonication.…”
mentioning
confidence: 99%